The Influence of Financial Literacy, Financial Attitudes, Sales Turnover, and Gender on MSME Financial Management Actors (Bilih Fish Souvenir Traders in Lake Singkarak) - Amanda, Putty Tri; Ferdawati, Ferdawati; Zahara, Zahara (Universitas Sultan Ageng Tirtayasa, 2025)
This study aims to determine and analyze the effect of financial literacy, financial attitudes, sales turnover, and gender on financial management actors. This research is quantitative research with multiple linear regression analysis methods. The population in this study were UMKM selling bilih fish souvenirs in Singkarak. The sample in this study were UMKM actors engaged in the trader sector. The sampling technique was carried out using purposive sampling method. The sample criteria in this study are UMKM traders oh bilih fish souvenirs who have their own product type of business. Respondents in this study totaled 75 respondents. Data collection in this study used a questionnaire with google form. The results showed that partially financial literacy and financial attitudes had an effect on UMKM financial management actors. Meanwhile, sales turnover and gender have no effect on UMKM financial management actors.